Implementation of the integrated public service information system application (SIPUT) to improve public service communication in the Loktuan Village, Bontang City - Fitriani, Karina Nur; Hairunnisa, Hairunnisa; Sucipta, Johantan Alfando Wikandana (International research journal of management, IT and social sciences, 2023)
SIPUT is an information system that utilizes information and communication technology to facilitate administrative management at the administrator level. The study aimed to find out the implementation of the SIPUT (Integrated Public Service System) application to improve public services in the Loktuan Village, Bontang City. This research used a descriptive qualitative approach with a purposive sampling technique. The primary data sources used in this study include the head of the Loktuan sub-district head, Mr. Hadi Jumianto and Mrs. Nurliya, and three public service employees or staff who operate the SIPUT application, as well as the surrounding community who often use public services in the Loktuan sub-district, as many as 5 people. Secondary data sources used are written sources. Data analysis using Miles and Huberman. In improving public services, five indicators serve as a benchmark for whether the efforts made can improve public service communication, namely fast service, appropriate service, cheap service, safe service, and fair service. The government can improve digital-based public services by adding additional features such as customer satisfaction levels and complaint telephone numbers if there are things that might harm citizens.